1996
DOI: 10.1128/aac.40.2.331
|View full text |Cite
|
Sign up to set email alerts
|

The anti-human immunodeficiency virus agent 3'-fluorothymidine induces DNA damage and apoptosis in human lymphoblastoid cells

Abstract: Patients infected with the human immunodeficiency virus experienced severe hematopoietic toxicity after treatment with the deoxynucleoside analog 3'-fluorothymidine (FLT). Using several methods for the analysis of genome integrity, including histochemical staining of the 3' ends of DNA and both conventional and pulsed-field agarose gel electrophoresis, we demonstrated that FLT caused extensive DNA fragmentation in CEM cells that was not observed when these cells were treated with other, less toxic thymidine an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 22 publications
(28 reference statements)
0
9
0
Order By: Relevance
“…The relative contribution of zidovudine to the increased lymphocyte apoptosis is unclear. Zidovudine and other nucleoside analogues have been shown to induce apoptosis in several in vitro systems [43–46]. In clinical studies of anti‐retroviral therapy however, the suppression of viral replication is not clearly associated with a decline in lymphocyte apoptosis [47–49].…”
Section: Discussionmentioning
confidence: 99%
“…The relative contribution of zidovudine to the increased lymphocyte apoptosis is unclear. Zidovudine and other nucleoside analogues have been shown to induce apoptosis in several in vitro systems [43–46]. In clinical studies of anti‐retroviral therapy however, the suppression of viral replication is not clearly associated with a decline in lymphocyte apoptosis [47–49].…”
Section: Discussionmentioning
confidence: 99%
“…DNA damage and unreliable replication can be induced by the backbone of antiretroviral therapy, namely NRTIs (Sundseth et al, 1996; Payne et al, 2011). NRTIs have been shown to inhibit the mitochondrial specific DNA polymerase-γ causing a decrease in mtDNA amount and quality.…”
Section: Haart-related Mitochondrial Toxicity In Agingmentioning
confidence: 99%
“…Additionally, antiretroviral therapy likely hastens the expansion of pre-existing mutations in mtDNA as depleted mtDNA pools display accelerated digression from their original genetic content (Khrapko, 2011; Payne et al, 2011). The NRTI 3′-deoxy-3′-fluorothymidine ( alovudine or FLT), known for its high toxicity, can cause DNA fragmentation and induce apoptosis (Sundseth et al, 1996). Interestingly, the NRTIs 3′-azido-3′-deoxythymidine ( zidovudine or AZT) and 2′,3′-didehydro-2′,3′-deoxythymidine ( stavudine or d4T) also disrupt telomerase maintenance and have telomere shortening effects, properties often related to cell senescence and aging (Strahl and Blackburn, 1994; Blasco, 2007).…”
Section: Haart-related Mitochondrial Toxicity In Agingmentioning
confidence: 99%
See 1 more Smart Citation
“…Side effects of alovudine are related to bone marrow damage, which includes liver toxicity and anaemia. Sundseth et al [239] reported that FLT caused extensive DNA fragmentation and induced apoptosis in CEM cells, providing a possible mechanism for its toxicity. In early clinical trials, the most common side effects reported were anaemia and neutropaenia.…”
Section: Nucleoside Rt Inhibitors In Clinical Developmentmentioning
confidence: 99%